Relationship between Promoter Hypermethylation of DNMT3A and DNMT3B genes and Endometrial Cancer - Masoumeh Omidali; Neda Jabbara; Golnaz Asaadi tehrani (Journal of Epigenetics, 2019)
Aberrant DNA methylation is an epigenetic event that occurs by methyltransferases. DNMT3A and DNMT3B are responsible for de novo methylation that plays important roles in normal development and disease. A number of reports on methylation of various genes in endometrial cancer have been published, but most of these studies focused on tumor suppressor genes. In this study, we determined the promoter methylation pattern of DNMT3A and DNMT3B genes; also we analyzed correlations between methylation statuses with clinicopathological parameters. 28 patients and 22 healthy controls were studied. Isolation of genomic DNA from FFPE and peripheral blood was performed and Methylation-Specific PCR (MSP) was applied for analysis the promoter CpG methylation status of DNMT3A and DNMT3Bgenes in the studied population. A significant difference was found between the study groups and the presence of promoter CpG hypermethylation status in the DNMT3A (P=0.04) gene. Furthermore methylation status between tissue and blood samples of DNMT3A genewas not significant (p=0.78). Our results indicated correlation between age and menopausal state with DNMT3B promoter methylation, but there were no significant relationships between parameters such as tumor grade, type of tumor, amount of metastasis and myometrium invasion, furthermore diabetes (p = 0.01) and obesity (p = 0.027) were two important items in endometrial cancer incidence. In our study hypermethylation of DNMT3A gene was found as an important event in carcinogenesis of endometrial cancer. The inactivation epigenetic of methylation regulation genes is a common occurrence in many cancers, including endometrial cancer.